2002
DOI: 10.1590/s0034-72992002000300009
|View full text |Cite
|
Sign up to set email alerts
|

Emissão otoacústica evocada transitória: instrumento para detecção precoce de alterações auditivas em recém-nascidos a termo e pré-termo

Abstract: Introdução:O diagnóstico e a intervenção precoces nas alterações auditivas são de fundamental importância no desenvolvimento infantil. O registro das emissões otoacústicas tem sido largamente indicado, por ser um exame rápido, de fácil aplicação. Objetivo: Os objetivos do presente estudo foram avaliar a função auditiva periférica de recém-nascidos a termo e pré-termo adequados e pequenos para a idade gestacional, por meio da pesquisa das emissões otoacústicas transitórias, identificando a prevalência de altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1
23

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 17 publications
3
14
1
23
Order By: Relevance
“…For TEOAE, this significant difference remained, showing matching results between the two types of OAEs. 14,15 The comparison group showed higher TEOAE and DPOAEs in relation to the study group.…”
Section: Discussionmentioning
confidence: 82%
“…For TEOAE, this significant difference remained, showing matching results between the two types of OAEs. 14,15 The comparison group showed higher TEOAE and DPOAEs in relation to the study group.…”
Section: Discussionmentioning
confidence: 82%
“…The age of bigger occurrence of problems on the middle ear is between 4 and 12 months (Saes, 2005). Garcia et al (2002) found a prevalence of conductive hearing loss in a population of 157 newborn of 29 ears out of 1000. Doyle et al (2004) related that fails on the hearing screening for TOAE also can be attributed to the alterations of the middle (secretor otitis) and that the children who present secretor otitis during the neonatal period present bigger risk to develop chronic middle otitis during the first year of life.…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of hearing loss in the group of prior term IC newborns is always bigger that in the group of term newborns, because of the fact that the first group have greater propensity for risk factors for hearing loss. Garcia et al (2002), studying 43 term children and 79 prior term children, observed that premature newborns fail more in the answers of the otoacoustic emissions. These authors found sensorioneural hearing loss for 16 ears out of 1000.…”
Section: Discussionmentioning
confidence: 99%
“…O diagnóstico e a intervenção precoces são de fundamental importância no desenvolvimento das crianças com alterações auditivas 1-4. Muito tem se falado da importância de realização de TAN logo após o nascimento 1,[5][6][7][8][9][10] . Os métodos objetivos mais utilizados são as emissões otoacústicas (EOA) e a audiometria de tronco cerebral (ABR) [9][10][11][12][13][14] .…”
Section: Introductionunclassified
“…As EOA têm sido largamente indicadas para programas de triagem por ser um exame rápido, de fácil aplicação e poder atingir um grande número de sujeitos em um curto espaço de tempo 1,6,10,12,16,17 .…”
Section: Introductionunclassified